The impact of learning Arabic via online games prototype among elementary learners in IIUM - Sahrir, Muhammad Sabri; Othman, Joharry; Zainuddin, Nurkhamimi; Osman, Nurulhuda; Muhammad , Ilyani Syiham; Md Ghalib, Mohd. Feham (2011)
This innovation features an online Arabic vocabulary learning games prototype spe-cifically designed for Arabic elementary learners at the pre-university level from Cen-tre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). This game-based learning prototype enables lecturers’ and students’ access to addi-tional Arabic language learning aid, in gaming application by complementing tradi-tional learning methods and tools. It facilitates vocabulary enhancement through a compendium and variety of mixed-genres of 34 games, in the online environment and supported with open sources of online dictionary, online translator, games glos-sary (English - Arabic) and vocabulary test games.